Literary aspects in the Holy Scriptures - Brînzea, Nicolae (Technium Social Sciences Journal, 2022)
The Bible, this impressive collection of scrolls or books, establishes a well-determined hierarchical relationship, from the literary perspective of the sacred text, which raises many interesting but also difficult questions, at least from the perspective of pertaining to a certain literary genre. Hermeneutically, it highlights valuable notions related to the aesthetics of the biblical text. The Bible is a written text, hence it is literature and belongs to literature, at the same time. From a literary point of view, the Scriptures are the inevitable book that enjoys an astonishing immanence. As a sacred text, the Scriptures have produced multiple forms of literature over time. The biblical text provides a set of suggestive and significant elements that require several ways of reading, but will never fully correspond to a given historical reality. The Bible has been and continues to be an inexhaustible source of inspiration for art creators of all times. The Scriptures can be considered a reference point in the conception process of the literary text, and the starting point of biblically inspired literature is represented by lyrical works such as the Song of Songs, Psalms, etc.